Prospecting and Identifying Phyllanthus amarus Lignans with Antileishmanial and Antitrypanosomal Activity - Conrado, Gabrielly Galdino; Grazzia, Nathalia; de Oliveira, Adriana da Silva S.; Franco, Caio Haddad; Moraes, Carolina Borsoi; Gadelha, Fernanda Ramos; Miguel, Danilo Ciccone; Garcia, Vera Lucia (Planta Medica, 2020)
Ten lignans (1 – 10) were isolated from the hexane-ethyl acetate extract of Phyllanthus amarus leaves. Three of them, cubebin dimethyl ether (3), urinatetralin (4), and lintetralin (7) are described for the first time in this species, while phyllanthin (1), niranthin (2), 5-demethoxyniranthin (5), isolintetralin (6), hypophyllanthin (8), nirtetralin (9), and phyltetralin (10) have been already reported from P. amarus. Among the lignans tested against Trypanosoma cruzi intracellular amastigotes, 2 was the most active with an EC50 of 35.28 µM. Lignans 2, 5, 7, and 9 showed inhibitory effects against Leishmania amazonensis promastigotes with EC50 of 56.34, 51.86, 23.57, and 43.27 µM, respectively. During in vitro infection assays, 5 reduced amastigotes by 91% at 103.68 µM concentration, whereas 7 and 9 reduced amastigotes by approximately 84% at 47.5 and 86.04 µM, respectively. Lignans 5, 7, and 9 were more potent in intracellular amastigotes with EC50 of 2.76, 8.30, and 15.83 µM, respectively, than in promastigotes. CC50 for all samples was > 100 µg/mL, thus revealing low cytotoxicity against macrophages, and selectivity against the parasite. L. amazonensis promastigotes treated with compounds 2 and 9 showed decreased respiratory control of 38% and 25%, respectively, suggesting a change in mitochondrial membrane potential and lower ATP production.
Keywords: Phyllanthus amarus; Euphorbiaceae; lignans; Leishmania amazonensis; Trypanosoma cruzi; amastigotes